2016
DOI: 10.1242/jcs.186403
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-I molecular motors at a glance

Abstract: Myosin-I molecular motors are proposed to play various cellular roles related to membrane dynamics and trafficking. In this Cell Science at a Glance article and the accompanying poster, we review and illustrate the proposed cellular functions of metazoan myosin-I molecular motors by examining the structural, biochemical, mechanical and cell biological evidence for their proposed molecular roles. We highlight evidence for the roles of myosin-I isoforms in regulating membrane tension and actin architecture, powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 135 publications
0
115
0
Order By: Relevance
“…Eight class I myosins are expressed in human and mice, encompassing six short‐tailed (Myo1a, Myo1b, Myo1c, Myo1d, Myo1g, and Myo1h) and two long‐tailed (Myo1e and Myo1f) myosins . Both short‐tailed and long‐tailed myosins have a TH1 (tail homology) domain enriched with basic amino acids, thus permitting its interaction with the plasma membrane.…”
Section: Class I Myosinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight class I myosins are expressed in human and mice, encompassing six short‐tailed (Myo1a, Myo1b, Myo1c, Myo1d, Myo1g, and Myo1h) and two long‐tailed (Myo1e and Myo1f) myosins . Both short‐tailed and long‐tailed myosins have a TH1 (tail homology) domain enriched with basic amino acids, thus permitting its interaction with the plasma membrane.…”
Section: Class I Myosinsmentioning
confidence: 99%
“…Schizosaccharomyces pombe (Myo1p), Saccharomyces cerevisiae (myo3p and myo5p), and Dictyostelium discoideum (MyoA, MyoE, MyoF, MyoB, MyoC, MyoD, and MyoH) have some paralogs of short and long tail myosins . MyoA, MyoE, MyoF, contain a TH1 region similar to Myo1c and Myo1g …”
Section: Class I Myosinsmentioning
confidence: 99%
“…The most prominent was myosin-Ic (Myo1c) (Fig. 4b), a member of class I myosin molecular motors, involved in regulating membrane tension, cell adhesion, and actin architecture 27 . Co-immunoprecipitation experiments confirmed that Myo1c associated with C-terminally-truncated, but also full length iASPP ( Fig.…”
Section: Myo1c Is a Partner Of Iaspp Involved In Spindle Positioningmentioning
confidence: 99%
“…Class I myosins are actin-binding motor proteins that typically function at sites of actin-based membrane deformation during cell shape changes. Humans have 8 class I myosins (Myo1a-h), whose expression and function differs across tissues (1). All class I myosins contain an Nterminal motor domain, a neck region that binds calmodulin or calmodulin-like light chains, and a short membrane-binding tail.…”
Section: Introductionmentioning
confidence: 99%